Infrastructure Governance and Economic Dynamics: Enhancing National Competitiveness from a Macroeconomic Perspective - Rokhadi; Setyawati, Heri Tugas; Novida, Diah Rachmawatie; Hariyanti; Mariyani, Dede (PT. LITERASI SAINS NUSANTARA, 2024)
Good infrastructure quality can be one of the key factors in enhancing Indonesia's economic competitiveness. With adequate infrastructure, companies can access markets more efficiently, reduce logistical costs, and increase productivity, all of which will enhance Indonesia's competitive advantage in the global market. This research aims to analyze infrastructure governance and social dynamics in enhancing national competitiveness from a macroeconomic perspective. The research method employed is a literature review with a qualitative approach and descriptive analysis. Data for this research were drawn from reliable academic sources, particularly from Google Scholar, covering the period from 2013 to 2023. The study results indicate that good infrastructure plays a crucial role in maintaining Indonesia's economic sustainability and enhancing national competitiveness. Smooth distribution of goods and services, new investment opportunities, economic inclusivity, and the development of specific sectors serve as tangible evidence of how adequate infrastructure can accelerate economic growth and societal well-being. However, significant challenges such as the need for substantial investment, effective risk management, and adaptability to global economic dynamics need to be carefully addressed to ensure the optimal realization of infrastructure benefits.